Voting is Social Work: Voices From the National Social Work Voter Mobilization Campaign. (2nd October 2019) - Abramovitz, Mimi; Sherraden, Margaret; Hill, Katharine; Smith, Tanya Rhodes; Lewis, Beth; Mizrahi, Terry
ABSTRACT: The National Social Work Voter Mobilization Campaign, also known as Voting is Social Work, involved social work faculty, field educators, practitioners, and students in a nonpartisan voter engagement drive. Following the 2018 elections, researchers surveyed Campaign participants in social work schools and agencies to document their voter engagement activities.The study reported extent and amount of their involvement. The survey distinguished between the voter engagement participation of school- versus agency-based social workers, which has not been studied elsewhere. Participants also reported the benefits of political participation to individuals, communities, and the profession and perceived barriers such as organizational constraints, fears of appearing partisan, and distrust of politics. Presented in historical context, the findings highlight the need to mainstream voter engagement throughout social work education.